ANESTEZJOLOGIA I INTENSYWNA TERAPIAInhaled nitric oxide effects outside the lungs – experimental and clinical evidence - Goździk, Waldemar; Goździk, Anna (Kardiochirurgia i Torakochirurgia Polska/Polish Journal of Thoracic and Cardiovascular Surgery, 2012)
New evidence indicates that nitric oxide inhalation leads to formation of new compounds which may be carried as thiol groups attached to protein in blood or act indirectly through nitrite and nitrate, metabolites which have been shown to elevate over time during exposure to inhaled NO. Additionally it has been shown that inhaled nitric oxide has no hemodynamic effects on normally perfused tissue, but increases blood flow selectively in ischemic tissue. It has a simple route of administration, safety profile and immediate action. Because of these properties, inhaled nitric oxide may serve as a rescue therapy for ischemic conditions in which collateral blood flow is important or until interventional or spontaneous reperfusion occurs. This review focuses on inhaled nitric oxide effects outside the lungs, and discusses its experimental and clinical applications, with particular attention to potential systemic effects of the gas.